The Securitization of Migration in Australian Policy under Prime Minister Tony Abbott (2013–2015) - Dinda Refi Utomo; Intan Putri Nuraini; Perbawani, Firsty Chintya Laksmi (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2026)
This study examines the securitization of migration in Australia during the administration of Prime Minister Tony Abbott (2013–2015), a period marked by a significant shift from a humanitarian-oriented migration approach toward policies emphasizing national security, territorial sovereignty, and border protection. Using Philippe Bourbeau’s The Securitization of Migration framework, this research analyzes how migration and asylum issues were constructed as security threats requiring extraordinary state responses. The study employs a descriptive qualitative method based on secondary data from government policy documents, legal regulations, academic journals, international human rights reports, and relevant literature. The findings indicate that migration securitization was manifested through institutional and security practice dimensions. Institutionally, it was reflected in the Migration Amendment Act 2013, the reintroduction of Temporary Protection Visas (TPVs), and the establishment of the Australian Border Force (ABF). In practice, securitization was implemented through Operation Sovereign Borders, maritime intercepttion and boat turn-back policies, and offshore processing centers in Nauru and Manus Island. These measures framed migration as a threat to national sovereignty and border integrity, legitimizing coercive and exclusionary migration controls while illustrating the tension between national security objectives and humanitarian principles.